Implementation of Accounting Information Systems for Small and Medium - Sized Enterprises in East Kalimantan, Balikpapan City - Muhammad Ari Purnomo; Hasan Mukhibad (Journal Research of Social Science, Economics, and Management, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting the national economy, particularly in creating employment opportunities and maintaining economic stability. However, many MSMEs still face challenges in financial management, especially in implementing accounting information systems (AIS). The lack of proper financial recording systems often makes it difficult for MSMEs to evaluate business performance and make accurate managerial decisions. This study aims to determine the implementation of accounting information systems in MSMEs in Balikpapan City and to identify the obstacles faced by MSMEs in adopting AIS for financial management and business development. This research uses a qualitative descriptive approach with a case study method. Data were collected through in-depth interviews, direct observation, and documentation involving seven informants consisting of company owners, finance managers, and shop owners in Balikpapan City. The data were analyzed using the Miles and Huberman qualitative analysis model, including data reduction, data presentation, and conclusion drawing. The findings indicate that most MSMEs in Balikpapan City have not implemented accounting information systems and still rely on manual recording methods using Microsoft Excel, Microsoft Word, and general ledger journals. Only a small number of businesses have implemented computerized systems such as Accurate software. The implementation of accounting information systems among MSMEs in Balikpapan City remains limited. Although AIS provides benefits such as improving efficiency and supporting managerial decision-making, its adoption is constrained by financial limitations, business scale, and the continued reliance on manual accounting practices.